New model of the vertical crustal movements in the area of Poland - Kowalczyk, Kamil (Geodesy and Cartography, 2012)
In 2003 the fourth levelling campaign has been finished in Poland. This campaign, together with the previous one carried out in 1974–1982, gave a very good opportunity to determine the land uplift in the area of Poland. The paper describes shortly the third and fourth campaigns, the computation of the relative land uplift, computation of land uplift referred to the mean sea level and modeling the land uplift by the least‐squares collocation method. Obtained results are compared with the computation done by the Institute of Geodesy and Cartography in 1986. Naujas vertikaliųjų žemės plutos judėsių Lenkijos territorijoje modelis Santrauka. 2003 m. Lenkijoje baigta ketvirtoji niveliacija. Šis darbas, kaip ir 1974–1982 m. atlikta trečioji niveliacija, sudaro geras prielaidas nustatyti Žemės plutos judesius Lenkijos teritorijoje. Trumpai aprašoma trečioji ir ketvirtoji niveliacija, santykinio Žemės plutos kilimo skaičiavimas, nustatomas Žemės plutos kilimas vidutinio jūros lygio atžvilgiu. Žemės plutos judesiai modeliuojami kolokacijos metodu. Gautieji rezultatai lyginami su 1986 m. Geodezijos ir kartografijos instituto skaičiavimų duomenimis. First published online: 03 Aug 2012